Biochemical interaction of twenty steroid derivatives with ribosomal protein kinase 4 S6 (RSK-4) surface using a theoretical model - Figueroa-Valverde, Lauro; Diaz-Cedillo, Francisco; Nexticapa, Marcela Rosas; Alvarez-Ramirez, Magdalena; López-Ramos, Maria; Melgarejo-Guttierrez, Montserrat; Cervantes-Ortega, Catalina; Mateu-Armad, Maria Virginia; Mijangos-Sanchez, Juliette (Brazilian Journal of Science, 2024)
Several genetic expressions have been involved in the development of cancer such as the expression of a ribosomal kinase S6 P90 (RSK-4). It is important to mention that some compounds such as LJH685, 2073047-06-8, and SL0101 can act as RSK-4 inhibitors; however, its interaction with the surface of RSK-4 is very confusing. The aim of this research was to evaluate the interaction of twenty-nine steroid derivatives (1 to 29) with of RSK-4 surface using 6rv2 protein, LJH685, 2073047-06-8 and SL0101 as theoretical tools in the Dockingserver program. The results showed differences in the aminoacid residues involved in the interaction of steroid derivatives with 6rv2 protein surface compared with LJH685, 2073047-06-8 and SL0101. Besides, the inhibition constant for steroid derivatives 1, 12, 14, 19 and 22 was lower compared to 2073047-06-8 drug. In conclusion, the steroid derivatives 1, 12, 14, 19 and 22 could be a good alternative as RSK-4 inhibitors to decrease cancer cells growth.